2022
DOI: 10.1186/s12884-022-04680-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of severe adverse perinatal outcomes among continuous birth weight percentiles on different birth weight charts: a secondary analysis of a cluster randomized trial

Abstract: Objective To identify neonatal risk for severe adverse perinatal outcomes across birth weight centiles in two Dutch and one international birth weight chart. Background Growth restricted newborns have not reached their intrinsic growth potential in utero and are at risk of perinatal morbidity and mortality. There is no golden standard for the confirmation of the diagnosis of fetal growth restriction after birth. Estimated fetal weight and birth wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Information on the SGA and LGA status of foetuses and infants is routinely used for improving obstetric and neonatal management. However, as previous studies have shown 14,15,23–26,38,41,42 and our study confirms, SGA or LGA diagnosis, when used in isolation without other predictors, performs poorly for predicting SNMM; in other words, the probability of SNMM is not materially changed by such a diagnosis. In our study, the expected rate of SNMM changed marginally from 20.2 per 1000 live births to 23.8, 36.1 and 54.4 per 1000 live births using a mild (10% increase in odds), moderate (50% increase) or extreme (100% increase) definition of SGA among female singletons at 39 weeks' gestation (Table 1).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Information on the SGA and LGA status of foetuses and infants is routinely used for improving obstetric and neonatal management. However, as previous studies have shown 14,15,23–26,38,41,42 and our study confirms, SGA or LGA diagnosis, when used in isolation without other predictors, performs poorly for predicting SNMM; in other words, the probability of SNMM is not materially changed by such a diagnosis. In our study, the expected rate of SNMM changed marginally from 20.2 per 1000 live births to 23.8, 36.1 and 54.4 per 1000 live births using a mild (10% increase in odds), moderate (50% increase) or extreme (100% increase) definition of SGA among female singletons at 39 weeks' gestation (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies, 14,15,[23][24][25][26]38,41,42 have shown that estimated foetal weight-or birthweight-for-gestational age indices perform poorly in terms of predicting serious neonatal morbidity and perinatal mortality. These studies used receiver-operatingcharacteristics (ROC) curves and area-under-the-curve methods, which are well-accepted methods for identifying the optimal cut-point of a biomarker for discrimination/prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Much of current research on FGR hinges on finding the best growth chart, definition, monitoring-management strategy and prediction model for adverse outcomes. The majority of studies reporting on these issues evaluate the incidence of a composite adverse perinatal outcome (CAPO) [10][11][12][13][14] . These CAPOs have obvious face value at first glance, however, we posit that their use can also be problematic.…”
Section: Use Of Composite Adverse Perinatal Outcomes In Fgr Studiesmentioning
confidence: 99%
“…Typically, SGA is defined as an abdominal circumference (AC), estimated fetal weight (EFW) or birth weight below the 10 th percentile (< p10). However, this approach is inherently flawed, because many SGA fetuses and newborns are constitutionally small, while some fetuses and newborns may not have reached their intrinsic growth potential despite having a weight above this cut-off 8,10,11 . Also, there is a risk of inadequate assessment of fetal size and growth due to the low sensitivity and specificity of sonographic fetal biometric measurements 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, many SGA fetuses and newborns are constitutionally small while on the other hand some fetuses and newborns with a weight above the cut-off may not have reached their intrinsic growth potential. 8,10,11 Also, there is a risk of inadequate assessment of fetal size and growth due to the low sensitivity and specificity of ultrasound fetal biometric measurements. 7 Currently, no tool exists that weighs fetal size against the unknown entity of intrinsic growth potential.…”
Section: Introductionmentioning
confidence: 99%